Vitamin D Receptor: A Novel Therapeutic Target for Kidney Diseases - Yang, Shikun; Li, Aimei; Wang, JianWen; Liu, Jun; Han, Yachun; Zhang, Wei; Li, Yan C.; Zhang, Hao (Current Medicinal Chemistry, 2018)
Background: Kidney disease is a serious problem that adversely affects human health, but critical knowledge is lacking on how to effectively treat established chronic kidney disease. Mounting evidence from animal and clinical studies has suggested that Vitamin D Receptor (VDR) activation has beneficial effects on various renal diseases. Methods: A structured search of published research literature regarding VDR structure and function, VDR in various renal diseases (e.g., IgA nephropathy, idiopathic nephrotic syndrome, renal cell carcinoma, diabetic nephropathy, lupus nephritis) and therapies targeting VDR was performed for several databases. Result: Included in this study are the results from 177 published research articles. Evidence from these papers indicates that VDR activation is involved in the protection against renal injury in kidney diseases by a variety of mechanisms, including suppression of RAS activation, anti-inflammation, inhibiting renal fibrogenesis, restoring mitochondrial function, suppression of autoimmunity and renal cell apoptosis. Conclusion: VDR offers an attractive druggable target for renal diseases. Increasing our understanding of VDR in the kidney is a fertile area of research and may provide effective weapons in the fight against kidney diseases.
Keywords: renal osteodystrophy